2013
DOI: 10.1108/pijpsm-05-2012-0039
|View full text |Cite
|
Sign up to set email alerts
|

Workplace stressors for investigative interviewers of child‐abuse victims

Abstract: Purpose-The purpose of this study is to identify the nature and prevalence of workplace stressors faced by interviewers of child sexual assault victims. Design/methodology/approach-Totally, 68 professionals (police and child protection workers) were invited to anonymously post their perceptions of workplace stressors on an internet forum as part of an investigative interviewing online training course. Specifically, participants were asked to reflect on salient sources of stress encountered in their role of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
3
22
0
3
Order By: Relevance
“…Consistent with previous research using a sample of more generalist child abuse investigators (Powell et al, 2013;Wright et al, 2006), exposure to case material was not an especially salient stressor. Stressors associated with ICE investigation related to three areas; work relationships, workload and resources and the physical environment.…”
Section: Resultssupporting
confidence: 89%
“…Consistent with previous research using a sample of more generalist child abuse investigators (Powell et al, 2013;Wright et al, 2006), exposure to case material was not an especially salient stressor. Stressors associated with ICE investigation related to three areas; work relationships, workload and resources and the physical environment.…”
Section: Resultssupporting
confidence: 89%
“…Prior research regarding police investigations of children related crimes such as neglect, homicide, or sexual abuse suggest that officers are often at greater risk for developing secondary traumatic stress (Krause, 2013; Chouliara et al, 2009; Powell and Tomyn, 2011). Officers working these cases may also be at risk for depression and anxiety (Powell and Guadagno, 2013; Russ et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Prior research regarding police investigations of children related crimes, such as neglect, homicide, or sexual abuse suggest that officers are often at greater risk for developing secondary traumatic stress (Krause, 2013; Chouliara, Hutchinson & Karatzias, 2009; Powell & Tomyn, 2011; Burns, Morley, Bradshaw & Domene, 2008; Violanti & Gehrke, 2004), and depression and anxiety (Powell & Guadagno, 2013; Russ, Lonne & Darlington, 2009). Powell and Guadagno (2013) also suggest that officers may be at higher risk for vicarious traumatization, a cumulative effect of trauma upon one’s self. Wright, Powell and Ridge (2006) found that the two key sources of negative work stress frequently associated with child abuse investigation were heavy caseloads and unavailability of formal coping mechanisms.…”
Section: Discussionmentioning
confidence: 99%